Heterogeneity among human collagenases demonstrated by monoclonal antibody that selectively recognizes and inhibits human neutrophil collagenase (The Rockefeller University Press, 1984)
The heterogeneity of human collagenases has been examined using a monoclonal antibody to neutrophil collagenase. This antibody inhibited collagenase activity and, when covalently coupled to Sepharose, bound both latent and active enzyme. Although human neutrophil collagenase was inhibited by the antibody, the activity of human skin and rheumatoid synovial collagenase was not significantly diminished in the presence of the antibody. Competitive inhibition studies also differentiated between these collagenases. Only human neutrophil collagenase effectively blocked the antibody in a competitive enzyme- linked immunosorbent assay while skin and rheumatoid synovial collagenase again failed to interact with the antibody. The unequivocal recognition of neutrophil collagenase as an immunologically distinct entity from other collagenases supports the hypothesis that neutrophil collagenase is a separate gene product from fibroblast or synovial collagenase.